Normalization of China-Indonesia's diplomatic relations and the role of the mianzi concept - Muas, R. Tuty Nur Mutia Enoch (UI Scholars Hub, 2012)
This thesis examines the normalization of China-Indonesia's diplomatic relations in order to understand China's main motivation. The